The Utility of Circulating Tumor DNA (ctDNA) Monitoring in Cancer Patients Who Are Pregnant or Planning to Become Pregnant - Stacey A. Cohen; Anup Kasi; Nicole Hook; Michael Krainock; Griffin Budde; Allyson Koyen Malashevich; Jeffrey Meltzer; Russ Jelsema; Perry Olshan; Paul R. Billings; Alexey Aleshin; Andrew S. Poklepovic (Hindawi Limited, 2022)
The number of pregnant women with cancer is on the rise. These patients and their providers encounter complex medical management decisions. Standard-of-care systemic therapy and radiological imaging can impair fetal development and affect viability. Conversely, insufficient monitoring and treatment can lead to cancer progression, compromising the health of the patient. Personalized and tumor-informed circulating tumor DNA (ctDNA) testing (Signatera™, bespoke mPCR NGS assay) is a validated, noninvasive blood test that can accurately assess cancer progression and tumor response to treatment ahead of radiological imaging, across solid tumors. In this case series of four patients, we explore the clinical utility of longitudinal ctDNA testing in the medical management of pregnant patients with solid tumors, to aid in informed decision-making for patients and providers.